Thinking ahead and staying in the present: Implications for reactivity to daily stressors. (15th July 2020) - Polk, Melody G.; Smith, Emily L.; Zhang, Ling-Rui; Neupert, Shevaun D.
Abstract: We examined how proactive coping and daily mindfulness may work together to predict emotional reactivity to daily stressors. Using data from the Mindfulness and Anticipatory Coping Everyday study (MACE; Neupert & Bellingtier, 2017 ; Neupert & Bellingtier, 2019 ), 116 older adults and 107 younger adults participated in a daily diary study for nine consecutive days. Results from multilevel models suggest that people high in proactive coping were more emotionally reactive to daily stressors on days with decreased mindfulness. Due to the trait-like future-oriented thinking of proactive coping and the state-like present-oriented aspect of daily mindfulness, these results underscore the importance of simultaneously considering state and trait information to elucidate antecedents, correlates, and consequences of daily stressors. Highlights: Emotional reactivity to daily stressors depends on both state and trait constructs. Trait-like proactive coping and state-like mindfulness affect daily stress outcomes. People high in proactive coping were vulnerable to decreases in daily mindfulness.